Complicit : How greed and collusion made the credit crisis unstoppable - Gilbert, Mark. (New York : Bloomberg Press, 2010)
"Reporter and editor Mark Gilbert plumbs the origins of the sub-prime debt crisis, tracing it back to 'a silent conspiracy of the well rewarded' in banking, real estate, trading, insurance, investing, politics, regulation, credit rating, law, and economic theory" - Provided by publisher.
Bubbles are for bathtubs : the real estate boom ; Unsafe at any rating : CDOs and the companies that judged them ; Priced for perfection : the financial gene pool economic Darwinism couldn't improve ; Bubbles, bubbles everywhere : global liquidity's search for a profitable home ; Judgment or luck : the profits banks couldn't understand - or protect ; Knight in rusty armor : an ill-advised rescue helps show banks just how much value their collateralized debt has lost ; The noose tightens : frozen money markets confound central bankers, hurt consumers, and drive imploding investments back onto bankers' books ; Central banks, unbalanced : caught off guard, the financial authorities make up the rules as they go along ; Et tu, money markets and municipals? : the crunch catches vanilla investments ; Giants fall : the credit crisis reaches its climax ; Conclusions and policy prescriptions.
Includes index.
Keywords: Subprime mortgage loans -- United States; Credit -- United States; Financial crises -- United States; Mortgage banks -- United States